Performance Test of Environmental Odour Measurement Instrument - Dede Heri; Arief Sabdo Yuwono; Erus Rustami; Daranrat Jaitiang (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Environmental odour assessment is important for evaluating air quality and community amenity; however, conventional dynamic dilution olfactometry requires specialised laboratory facilities and costly equipment, limiting its use for routine field monitoring. This study developed and evaluated a direct-airflow environmental odour measurement instrument that delivers ambient air directly to panellists without dilution. The instrument was designed to operate at an airflow velocity of 1 m/s, selected through climatological analysis, panellist preference testing, and technical verification against ASHRAE Standard 55 and EN 13725:2022. Eight screened panellists assessed ambient air, n-butanol, and ammonia using the Yuwono Hedonic Scale under field conditions. Instrument performance, panellist consistency, and the influence of meteorological conditions on odour perception were evaluated. The selected airflow velocity of 1 m/s yielded the highest ratings for odour detectability, comfort, and ease of assessment. Repeated ammonia measurements (3.4–3.5 ppm) produced highly consistent hedonic scores (−3.2 to −3.0), while ammonia concentration and hedonic scores followed a logarithmic relationship (R² = 0.9994). Mean hedonic scores for ambient air (−0.1), n-butanol (−1.3), and ammonia (−3.1) confirmed consistent panellist discrimination of odour characteristics.